Experimental and kinetics study on oxidation of three‐component in supercritical water. (17th February 2019) - Zhang, Jie; Lu, Jinling; Chen, Senlin; He, Denghui; Huang, Rui; Luo, XingQi
ABSTRACT: The supercritical water oxidation of a methanol, acetic acid, and phenol mixture was investigated in this study. The experimental design was accomplished by means of response surface methodology. 16 experimental runs were performed in a continuous tubular reactor. Quadratic polynomial equations with a satisfactory data fit and accuracy were established on the basis of the experimental results. The calculation results demonstrate the promotion behaviour of methanol, the inhibition behaviour of acetic acid, and the positive effect of phenol on the supercritical water oxidation of the ternary mixture. The interactive effect of the mechanism was characterized by means of the computational simulation with the mechanism‐based kinetic model. It seems that the positive influence of methanol was derived from the co‐oxidation effect of the methanol in the destruction of both acetic acid and phenol. The oxidation of acetic acid was restrained in the mixture system, which is attributed to the more favourable radical capture for phenol, and, thus, the overall disappearance kinetics was retarded with the addition of acetic acid. Finally, the co‐oxidation enhancement of both methanol and acetic acid related to phenol oxidation in supercritical water contributed to the positive effect of phenol on mixture oxidation efficiencies.